Interlayer Engineering of KxMnO2 Enables Superior Alkali Metal Ion Storage for Advanced Hybrid Capacitors. Issue 12 (20th June 2022) - Chen, Lina; Zhang, Yamin; Hao, Chongyang; Zheng, Xiaowen; Sun, Qidi; Wei, Youri; Li, Bohao; Ci, Lijie; Wei, Jun
Abstract: The lack of ideal cathode materials is a great challenge in the development of hybrid capacitors based on various alkali metal ions. In this work, potassium‐ion pre‐intercalated K x MnO2 nanowires with enlarged interplanar spacing and optimized ion diffusion channels are successfully obtained through a hydrothermal process, and exhibit superior electrochemical property in lithium‐, sodium‐, and potassium‐ion‐based hybrid supercapacitors (HSCs). The potassium‐ion hybrid supercapacitor (KIC) assembled with a K x MnO2 cathode and activated carbon anode delivers a high energy density of 49.2 Wh kg −1, a high power density of 4.7 kW kg −1, and outstanding cycling performance up to 7000 cycles with almost no capacitance decay, which outperforms most of the KICs reported previously. This ion intercalation engineering provides a strategy to design high‐performance cathodes for hybrid capacitors and other battery systems. Abstract : Give a little KIC : Potassium‐ion pre‐intercalated K x MnO2 nanowires with enlarged interplanar spacing and optimized ion diffusion channels are successfully obtained through a hydrothermal process, and exhibit superior electrochemical properties in lithium‐, sodium‐, and potassium‐ion‐based hybrid supercapacitors (HSCs). A potassium‐ion hybrid supercapacitor (KIC) assembled with a K x MnO2 cathode and activated carbon anode delivers a high energy density of 49.2 Wh kg −1, a high power density of 4.7 kW kg −1, and outstanding cycling performance up to 7000 cycles with almost no capacitance decay, which outperforms most previously reported KICs.